The analysis of the equipment expenses for bit-serial arithmetic devices in golden 1-propotion numerical system - Азаров, Олексій Дмитрович; Черняк, Олександр Іванович (Problems of Informatization and Control, 2012)
The expenses of the equipment comparative analysis is given at devices construction for bit-serial adding and subtraction in golden 1-propotion numerical system. It showed, that using of the complement codes with signs in any forms reduces the expenses of the equipment comparative to using minimizing forms of two's complement codes